Pre-harvest illumination with different spectral compositions improves quality of green oak lettuce in hydroponic system - Htwe, Nang Myint Phyu Sin; Rattanaphan, Thawat; Bourchookarn, Apichai; Sirinupong, Manoon; Ruangrak, Eaknarin (Agriculture and Natural Resources, 2023)
Importance of the work: Pre-harvest illumination has an impact on the nutritional value of vegetables by improving antioxidants and regulating nitrate concentration. Objectives: To focus on the effect of pre-harvest illumination with different spectral compositions and photoperiods on the nitrate content, total phenolic content (TPC) and antioxidant capacity of hydroponic green oak lettuce. Materials & Methods: This experiment was arranged in a completely randomized design with three replications. The 10 treatments comprised no treated light (control) and pre-harvesttreatments with different spectral compositions of blue 460 nm-to-red 630 nm-to-red 660 nm as BRR 1:1:1 and BRR 2:1:1, respectively, and fluorescence light (FL) for 1 d, 2 d or 3 d (1D, 2D or 3D, respectively). Results: The hydroponic green oak lettuce under pre-harvest lighting of 1D-BRR 1:1:1 contained the significantly lowest nitrate content of 14.36 mg/g which was a 67% reduction from the control. The TPC was the significantly highest in 3D-BRR 2:1:1 at 78.29 µg gallic acid equivalent (GAE)/g dry weight (dw), which was 59% greater than for the control. The 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay resulted in the significantly highest scavenging activities in the plant treated with 2D-BRR 2:1:1 (265.49 µg GAE/ g dw), which was 53% greater than the control. However, the results for both the TPC and DPPH were not significantly different from that of 1D-BRR 1:1:1. Main finding: Among the pre-harvest illuminations treatments investigated with different spectral compositions, 1D-BRR 1:1:1 produced the lowest nitrate content, whereas the TPC and scavenging activity of hydroponic green oak lettuce were not significantly different for the 2D-BRR 2:1:1 and 3D-BRR 2:1:1 treatments. Therefore, 1D-BRR 1:1:1 pre-harvest illumination can be recommended for green oak lettuce production in a hydroponic system.